Peripheral neuropathy as the presenting feature of tyrosinaemia type I and effectively treated with an inhibitor of 4-hydroxyphenylpyruvate dioxygenase. - Gibbs, T C (1993)
A 21 month old girl presented with a short history of frequent falls and a right sided foot drop. She went on to suffer recurrent episodes of distal weakness in her arms and legs with hyporeflexia. Electrophysiological studies were consistent with inflammatory demyelinating polyradiculoneuropathy (IDP) and treatment with corticosteroids appeared to lead to an improvement. However, the development of hypertension, evidence of tubulopathy, and hepatomegaly led to re-evaluation. A diagnosis of type I tyrosinaemia was made, based on increased urinary excretion of succinylacetone and decreased activity of fumarylacetoacetase in her cultured skin fibroblasts. A low tyrosine diet did not prevent life-threatening exacerbations of neuropathy but intravenous haemarginate appeared to aid her recovery from one exacerbation. An immediate improvement in strength was seen after starting treatment with 2-(2-nitro-4-trifluoro-methyl-benzoyl)-1,3-cyclohexanedione (NTBC), an inhibitor of 4-hydroxy-phenylpyruvate dioxygenase. A liver transplant was performed but the patient died of immediate postoperative complications. Tyrosinaemia needs to be considered in a child with recurrent peripheral neuropathy because (i) the signs of liver disease and renal tubular dysfunction may be subtle; (ii) acute exacerbations may be life threatening; (iii) specific forms of treatment are available.